2013
DOI: 10.1099/jmm.0.052043-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cobas TaqMan MTB real-time PCR assay for direct detection of Mycobacterium tuberculosis in respiratory specimens

Abstract: The Cobas TaqMan MTB assay is a real-time PCR (qPCR) kit for rapid detection of Mycobacterium tuberculosis from clinical specimens. There are, however, limited studies validating its performance. We performed a prospective study in two hospitals in Taiwan on 586 respiratory specimens. By using culture as the reference method, the sensitivity and specificity of the Cobas TaqMan MTB assay were found to be 82.7 and 96.5 %, respectively. The sensitivity of the Cobas TaqMan MTB assay in acid-fast stain-negative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…According to previous studies, the sensitivity and specificity ranges of the Cobas assay are 71.4% to 97.2% and 95.8% to 100%, respectively (6)(7)(8)(9)(10)(11)(12)(13). The sensitivity (78.8%) and specificity (99.5%) of the Cobas assay in this study were also quite similar to those seen in our previous studies (6,7).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…According to previous studies, the sensitivity and specificity ranges of the Cobas assay are 71.4% to 97.2% and 95.8% to 100%, respectively (6)(7)(8)(9)(10)(11)(12)(13). The sensitivity (78.8%) and specificity (99.5%) of the Cobas assay in this study were also quite similar to those seen in our previous studies (6,7).…”
supporting
confidence: 77%
“…There were two false-positive specimens misidentified by the Cobas assay that were smear negative. The low (40.0%) sensitivity with smear-negative specimens is a limitation of these assays (10). Note that there were no invalid results produced by the Genedia assay.…”
mentioning
confidence: 99%
“…1 ). Twenty-one [ 10 , 24 , 25 , 27 , 29 , 31 , 32 , 39 , 44 , 45 , 47 , 49 , 51 , 52 , 54 , 57 , 60 , 61 , 64 , 66 , 67 ] reported detection of pulmonary TB (PTB), fifteen [ 23 , 30 , 33 , 35 , 37 , 38 , 40 42 , 50 , 53 , 55 , 56 , 59 , 62 ] reported detection of extra-pulmonary TB (EPTB) and ten [ 26 , 28 , 34 , 36 , 43 , 46 , 48 , 58 , 63 , 65 ] reported on both types of pathological sample. Table 1 summarises the main characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The CobasTaq-Man MTB assay, which includes two major steps of DNA extraction and PCR amplification, is conducted according to the manufacturer's instructions 17 . Studies have shown that the CobasTaqMan MTB assay is at least as sensitive as its predecessor, the CobasAmplicor MTB system 18 19 . Commercial assay such as the CobasAmplicor MTB assay or CobasTaqMan MTB assay has been widely used in clinical mycobacteriology laboratories for direct specimen detection of MTBC DNA in the past 20 years 20 21 .…”
Section: Molecular Methods In Tb Diagnosismentioning
confidence: 99%